1997
DOI: 10.1292/jvms.59.695
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gestagen Concentration in Feces Using a Bovine Milk Progesterone Quantitative Test EIA Kit and Its Application to Early Pregnancy Diagnosis in the Sow.

Abstract: ABSTRACT. We attempted to measure the gestagen concentration in the feces of pigs by using a commercial bovine milk progesterone quantitative test EIA kit, and investigated the possibility of applying of this method of gestagen concentration measurement to early pregnancy diagnosis in the sow. Feces were collected from the rectum of the pig, and 0.5 g of the feces was placed in 20 ml of distilled water, stirred, and centrifuged. The supernatant was used as the fecal solution for measurement of gestagen. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Feces was collected and preserved according to a method described in a previous report [18]. Fecal collection was carried out while each sow remained unrestrained in her stall.…”
Section: Fecal Collection and Fecal Solution Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…Feces was collected and preserved according to a method described in a previous report [18]. Fecal collection was carried out while each sow remained unrestrained in her stall.…”
Section: Fecal Collection and Fecal Solution Preparationmentioning
confidence: 99%
“…Because the previous study [18] showed that the criterion for positive pregnancy diagnosis was a gestagen concentration of more than 200 ng/g of fecal weight or 5 ng/ml of fecal solution [18], a standard fecal solution was prepared with at a progesterone concentration of 5 ng/ml. The method of preparation was the same as that used in the previous study [18].…”
Section: Standard Gestagen Fecal Solution Preparationmentioning
confidence: 99%
See 3 more Smart Citations